1983
DOI: 10.1177/00220345830620091101
|View full text |Cite
|
Sign up to set email alerts
|

A Microradiographic and Chemical Comparison of in vitro Systems for the Simulation of Incipient Caries in Abraded Bovine Enamel

Abstract: An acetate buffer system, supersaturated with fluorapatite but not with hydroxyapatite, produced lesions in abraded bovine enamel which resembled human enamel caries lesions, both morphologically and in their F distribution. A gelatin-lactate system gave similar results when unpurified gelatin was used. Systems containing deionized gelatin, diphosphonate, or Ca and phosphate but no F, failed to produce caries-like lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
1
4

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 21 publications
6
40
1
4
Order By: Relevance
“…Previous studies have demonstrated that an aqueous phase unsaturated with respect to both hydroxyapatite and fluorapatite erodes the enamel irrespective of the fluoride concentration in contrast to a solution unsaturated with respect to hydroxyapatite and supersaturated with respect to fluorapatite that results in a caries-like lesion [Larsen, 1972[Larsen, , 1973ten Cate and Duijsters, 1983;Pearce, 1983;Margolis et al, 1986]. The supersaturation with respect to fluorapatite induces an uptake of fluoride in the surface enamel through fluorhydroxyapatite formation [Larsen, 1973;Pearce, 1983], resulting in preservation of the surface layer. In the present study, all soft drinks were strongly unsaturated with respect to both hydroxyapatite and fluorapatite (table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that an aqueous phase unsaturated with respect to both hydroxyapatite and fluorapatite erodes the enamel irrespective of the fluoride concentration in contrast to a solution unsaturated with respect to hydroxyapatite and supersaturated with respect to fluorapatite that results in a caries-like lesion [Larsen, 1972[Larsen, , 1973ten Cate and Duijsters, 1983;Pearce, 1983;Margolis et al, 1986]. The supersaturation with respect to fluorapatite induces an uptake of fluoride in the surface enamel through fluorhydroxyapatite formation [Larsen, 1973;Pearce, 1983], resulting in preservation of the surface layer. In the present study, all soft drinks were strongly unsaturated with respect to both hydroxyapatite and fluorapatite (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental background for the effect of fluoride in the caries process is that as enamel dissolves due to an undersaturation with respect to hydroxyapatite the aqueous phase remains supersaturated with respect to fluorapatite which is formed in the surface layers of the enamel [Larsen, 1973[Larsen, , 1974. The more supersaturated with respect to fluorapatite the thicker and more mineralized becomes the surface layer and the less demineralized the lesion body enamel [Larsen, 1974;ten Cate and Duijsters, 1983;Pearce, 1983]. When the aqueous phase is unsaturated with respect to fluorapatite a surface layer is not formed at all and the lesion developed is therefore not a caries-like lesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various gel systems have been used in studies of enamel demineralization [Gray and Francis, 1963;Manson-Hing et al, 1972;Ingram and Silverstone, 1981;Pearce, 1983], including gelatin gels con taining lactic acid which produce incipient caries of enamel that mimic natural le sions [Silverstone, 1966]. The ultrastructu-ral characteristics of the incipient enamel lesion are directly attributable to reminer alization within the lesion during lesion progression or partial regression.…”
mentioning
confidence: 99%
“…The reason for taking scans in triplicate was the observation [de Groot et al, 1986] that caries lesions in intact human enamel are often inhomogeneous. Abraded bovine enamel demineralizes more homogeneously [Pearce, 1983;ten Cate and Duysters, 1983], al though inhomogeneity has been reported for these preparations too [ten Bosch et al, 1984]. The scans were chosen near the separation notch lying between the treated and nontreated enamel areas.…”
Section: Caries Lesion Formation and Microradiographymentioning
confidence: 99%